(untitled) (Global Journal of Medical Research, 2024)
Heart transplants while life-saving come with significant trauma a full chest incision long recovery periods and a high risk of complications In just two and a half hours a 16-year-old boy s failing heart was replaced without a full chest incision This was the world s first fully robotic heart transplant in which the technique has undergone a US patent called the Khaliel Technique 63 694512 This game-changing procedure is one of today s healthcare milestones challenging the limitations of traditional surgery While this and other feats - like the world s first fully robotic liver transplant - demonstrate the power of robotic systems in elevating surgical precision and improving outcomes the effective integration of robotics in surgery relies on three fundamental pillars advanced technology meticulous planning and team collaboration With the right approach we can open new doors to better healthcare particularly in critical procedures where the margin for error is razor-thin